DIC Analysis of Prefabricated Fractured Coal Specimens under Stepwise Constant-Amplitude Cyclic Loading - Wang, Lei (International Journal of Natural Resources and Environmental Studies, 2025)
The mechanical response characteristics of coal-rock masses containing structural defects in mining roadways, under engineering disturbances, are prone to inducing dynamic instability phenomena in surrounding strata, such as roof collapse and rib spalling. These dynamic hazards pose a significant threat to the safe extraction of deep resources. Therefore, this paper takes coal-rock samples from Shendong mining area as the research object, designs stepwise constant-amplitude cyclic loading-unloading tests, and utilizes rock fatigue testing machine and DIC equipment to analyze in detail the strain field evolution process and final failure mode of prefabricated fractured coal samples under cyclic loading. The results demonstrate that prefabricated fractures play a significant controlling role in crack initiation, propagation and coalescence, and dominate the final failure mode of specimens.